PENGGUNAAN JASA DEBT COLLECTOROLEH PIHAK BANK DALAM PENAGIHAN KREDIT MACET PADA KARTU KREDIT - Feri Andrianton (Universitas 17 Agustus 1945 Samarinda, 2020)
ABSTRACTPayment using a credit card will charge a very high interest. The interest is very high, causing many people who can not pay their debts to the bank so it requires a great effort for the bank to collect credit card debt. To collect the debt, the Bank can use various methods even the bank is not reluctant to hire debt collector servicesThe type of research the author uses is Normative legal research. Normative Legal Research (normative juridical) is a legal research method carried out by examining mere literature or secondary data.The results of the study stated that based on the results of research conducted by the author of Bank CIMB NIAGA Cab. Kutai Kartanegara can be concluded that the use of debt collectors by banks in the use of bad credit on credit cards by using threats and even violence against customers can be categorized as a crime in the perspective of criminal law. Namely with Article 310 in conjunction with Article 335 paragraph (1) and jo Article 170 of the Criminal Code and the conditions for the use of debt collector services by banks in the collection of bad credit on credit cards according to applicable regulations is if the quality of credit card bills has entered into doubtful or bad collectibility. , Billing of other parties is done in a way that is not violating the law and In a cooperation agreement between the issuer & other parties to collect credit card transactions, it must contain a clause concerning the issuer's responsibility for any legal consequences of the cooperation of other parties.Keywords: Credit, Loss, Debt Collector